2016
DOI: 10.1142/s0218271816500644
|View full text |Cite
|
Sign up to set email alerts
|

Wormhole geometries in fourth-order conformal Weyl gravity

Abstract: We present an analysis of the classic wormhole geometries based on conformal Weyl gravity, rather than standard general relativity. The main characteristics of the resulting traversable wormholes remain the same as in the seminal study by Morris and Thorne, namely, that effective super-luminal motion is a viable consequence of the metric.Improving on previous work on the subject, we show that for particular choices of the shape and redshift functions the wormhole metric in the context of conformal gravity does… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…Hermann Weyl [30,31] introduced conformal gravity or Weyl gravity, for cosmology conformal gravity is also of concern. Tanhayi et al [32] shown that the estimated value of cosmological constant and Hubble parameter are close to their measured values. They studied the dependence of Hubble parameter and cosmological constant in Weyl gravity, as a function of t and r. Ghanaatian et al [33] considered the modified gravity coupled by Weyl tensor in spatially flat Friedmann-Lemaître-Robertson-Walker (FLRW) metric, they described the cosmic expansion of the universe also they checked stability conditions of models.…”
Section: Introductionmentioning
confidence: 68%
“…Hermann Weyl [30,31] introduced conformal gravity or Weyl gravity, for cosmology conformal gravity is also of concern. Tanhayi et al [32] shown that the estimated value of cosmological constant and Hubble parameter are close to their measured values. They studied the dependence of Hubble parameter and cosmological constant in Weyl gravity, as a function of t and r. Ghanaatian et al [33] considered the modified gravity coupled by Weyl tensor in spatially flat Friedmann-Lemaître-Robertson-Walker (FLRW) metric, they described the cosmic expansion of the universe also they checked stability conditions of models.…”
Section: Introductionmentioning
confidence: 68%
“…The sphere at r = r 0 is mapped to the throat of the wormhole. The relation 16) implies, that the transformation (2.12) can be equivalently characterised in terms of r ± . According to (2.13) r can become infinite or even negative for |η 0 | < π/2.…”
Section: Domain Of the Transformationmentioning
confidence: 99%
“…In fact, in the context of f (R) theories of gravity, the solution of wormholes have attracted much attention where wormholes can be theoretically constructed with the presence of normal matter [26,27]. This type of solutions were also found in f (T ) gravity [28,29], hybrid metric-Palatini theory [30], multimetric gravity [31], Rastall gravity [32], conformal Weyl gravity [33,34], modified gravity [35], Horndeski theory of gravity [36] and other theories.…”
Section: Introductionmentioning
confidence: 97%